Đổi mới rèn luyện nâng lực dạy học trong thực tập sư phạm của sinh viên đại học sư phạm kĩ thuật theo tiếp cận năng lực thực hiện - Vũ, Xuân Hùng (Viện KHGD Việt Nam, 2020)
This article presents study on drilling of teaching abilities in pedagogical practice by technical teacher trainees using performance approach. The study clarifies characteristics and hindrances for teaching ability drilling in pedagogical practice among technical teacher trainees based on performance approach on goal, content, process and assessment changes for improved quality